Grampian Health Board's joint drug formulary. Issue 6756 (13th October 1990) - Garvey, G; Jappy, B; Stewart, D; Williams, A; Duffus, P R; Maitland, J M; Valentine, M J; Wedderburn, S; Webster, J; Petrie, J C
Abstract : OBJECTIVE--To develop a model for creating a joint general practice-hospital formulary, using the example of ulcer healing drugs. DESIGN--A joint formulary development group produced draft guidelines based on an earlier hospital formulary, which were sent to interested local general practitioners for consultation. Revised guidelines were then drawn up and forwarded to the health board's medicines committee for approval and distribution. SETTING--Grampian Health Board. SUBJECTS--Nine members of joint formulary development group plus local general practitioners who were invited to comment on a list of 11 ulcer healing drugs. MAIN OUTCOME MEASURE--Degree of coincidence of drugs selected by hospital doctors and general practitioners. RESULTS--The ulcer healing drugs selected by the panel of general practitioners and by hospital doctors were highly coincident. The cost of one day's treatment with drugs varied considerably between hospital and general practice--for example, one drug cost 46p in hospital and 1 pounds in general practice and another cost 1.26 pounds in hospital and 1.01 pounds in general practice. Overall, six drugs cost more in hospital and five cost more in general practice. CONCLUSIONS--A joint formulary for use in hospitals and general practice in a health board can be devised fairly simply by consultation as virtually the same drugs are used in both types of practice. It should influence the health board's expenditure on drugs and affect the choice of drugs when a patient is discharged from hospital or is referred to any hospital in the region.